General And Specific Features In Realizing An Essay In English Language – A Case Study Of Essay On Economic Themes - TASCOVICI, Daliana Ecaterina; Dragomir, Robert; PLATON, Carolina (Annals of Spiru Haret University. Economic Series, 2016)
The present paper wants to be a systematic and not only a theoretical approach on essays. This type of writing knows several points of view connecting its form, content, specific features and types, rules to be observed in its writing, structures or styles. As we know, it implies freedom of composition, originality, associations of surprising images and propensity for aphorism. We try to frame all its specifications within the economic essay, as economics is a field of exact utterance, where the speaker cannot play with the words and their meaning.